2013
DOI: 10.1128/jb.02164-12
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-Ray Scattering for Imaging of Surface Layers on Intact Bacteria in the Native Environment

Abstract: Crystalline cell surface layers (S-layers) represent a natural two-dimensional (2D) protein self-assembly system with nanometerscale periodicity that decorate many prokaryotic cells. Here, we analyze the S-layer on intact bacterial cells of the Gram-positive organism Geobacillus stearothermophilus ATCC 12980 and the Gram-negative organism Aquaspirillum serpens MW5 by smallangle X-ray scattering (SAXS) and relate it to the structure obtained by transmission electron microscopy (TEM) after platinum/ carbon shado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…For SAXS data evaluation, the value for wild-type cells was subtracted from the value for S-layer-deficient cells. After division of the signal by the form factor for infinite plates, the intensity modulations were interpreted as the structure factor to determine the size and arrangement of the two glycoproteins TfsA-GP and TfsB-GP (Sekot et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SAXS data evaluation, the value for wild-type cells was subtracted from the value for S-layer-deficient cells. After division of the signal by the form factor for infinite plates, the intensity modulations were interpreted as the structure factor to determine the size and arrangement of the two glycoproteins TfsA-GP and TfsB-GP (Sekot et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Small-angle X-ray scattering (SAXS) offers another option for determining the structure of biological macromolecules in different environments under conditions close to those in physiological settings (Svergun and Koch, 2003). Its application to S-layer research on intact bacteria was demonstrated recently (Sekot et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After the T. forsythia S-layer had been found to delay the host immune response, at least at the early stage of infection, (Sekot et al 2011), a detailed investigation of the bacterium’s cell surface architecture (Sekot et al 2013) and glycosylation ensued (Posch et al 2011). As previously mentioned, the S-layer of the ATCC 43037 type strain was shown to be modified with an O -linked oligosaccharide containing several rare sugar residues (Figure 1B), including a Pse derivative with an N -acetimidoyl (Am) group at C-5 and an N -glyceroyl (Gra) group at C-7 (Pse5Am7Gra; Figure 1A; (Sekot et al 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include welldescribed virulence factors such as the leucine-rich-repeat protein BspA [2,3] and the protease PrtH/Fdf [4]. The T. forsythia cell surface (S-) layer was described to consist of the alternating TfsA and TfsB glycoproteins that have their corresponding genes located next to each other in the genome [5][6][7] and align in a 2D lattice, which drastically impacts the host immune response [8][9][10]. In T. forsythia, the S-layer proteins as well as other cell surface proteins are modified with a complex O-glycan that can be dissected in a species-specific portion and a core saccharide that is proposed to be conserved in the Bacteroidetes phylum of bacteria [6,10,11].…”
Section: Introductionmentioning
confidence: 99%